Knowledge, attitude, and practice of influenza vaccine immunization among primary healthcare providers in Dubai health authority, 2016-2017 - Lateefa Mohamed AlMarzooqi; Anfal Ali AlMajidi; Abeer Abdulrahim AlHammadi; Noura AlAli; Hamda Hassan Khansaheb (Taylor & Francis Group, 2018)
Background: Vaccination of healthcare providers (HCPs) against seasonal influenza has been consistently recommended worldwide. Despite that, healthcare providers (HCPs) globally and in other Middle Eastern countries continue to have a low rate of influenza vaccination due to various reasons. No data are available from our country, United Arab Emirates. Objectives: To identify the percentage of vaccinated HCPs, identify the most common reason for receiving the vaccine or not and to identify the level of HCPs knowledge towards the influenza vaccine itself. Methods: Using a cross-sectional study design, anonymous 18-item self-administered questionnaires were distributed among healthcare providers in the 11 primary healthcare centers of Dubai Health Authority over a period of 5 months. Results: Of the 431 participants who completed the questionnaires, 53.4% reported getting vaccinated. The difference in the vaccine uptake between the different professional categories was significant [P value < .000].The most common reason reported by HCPs for getting the vaccine was to protect themselves (94.8%). Of the 46.6% who did not accept the vaccine, the most common reason for not being vaccinated was their belief of not being at high risk to contract influenza (39.8%). Despite fairly good knowledge (63.3%), healthcare providers continue to have their reservations with regards to the yearly influenza vaccination. Conclusion: Although our HCPs attitude towards vaccine uptake, knowledge and practice were positive; the misconception about the vaccine remains the main reason for not being vaccinated as per our study findings. Overall, the study results raise hope of prospective increase in vaccination through educational and technical interventions and by increasing physician involvement. One suggested method would be to apply mandatory vaccination policies since voluntary vaccinations have shown lesser than satisfactory results and to be integrated in the online staff file system to be able to verify the uptake, in addition to provide easily accessible vaccine centers, during the season in order to facilitate tracking and verification of the vaccination status & to encourage staff compliance.